Attenuation of Cardiomyopathy Induced in Sub-Chronic Exposure of Acrolein by Sulforaphane via Indirect PPARy Expression Promoter - Emeka, Promise Madu; Ibrahim, Hairul-Islam Mohamed; Morsy, Mohamed Aly; Alhaider, Ibrahim Abdulraham; Hussian, Snawar; Ahmed, Emad Abdelaziz (Indian Journal of Pharmaceutical Education and Research, 2021)
Sulforaphane (SPN) is reported to activate the Nrf2/Keap1 complex responsible for protein and gene expression promotion of various antioxidant enzymes. The present study examined the role of Nrf2 in modulating other signaling pathways involved in SPN’s attenuation of acrolein (ACL)-induced cardiomyopathy in rats. Forty-two rat was categorized into seven 4-week treatment groups: control, SPN, losartan (LTN), ACL, ACL+SPN, ACL+LTN, and ACL+SPN+LTN. Heart samples were harvested for analysis; cardiac oxidative and injury biomarker levels and histopathological examination were undertaken. PPARγ, Nrf2, NF-κB, COX-2, and CYP2E1 protein expressions were examined. Results show that SPN and SPN+LTN reduced GSH, catalase, and lipid peroxidation compared to the ACL-treated group. Also, levels of creatine kinase-MB, cardiac troponin, and caspase 3 induced by ACL were all attenuated. Altered cardiac tissue pathophysiology by ACL was alleviated. SPN+LTN significantly increased Nrf2 expression via PPARγ action but decreased NF-κB and COX-2 expressions. Also, ACL increased CYP2E1 expression was significantly attenuated by the SPN+LTN combination. For the first time, it suggests that SPN+LTN might offer a better therapeutic alternative to ACL-induced cardiomyopathy by activating Nrf2 via PPARγ and reducing NF-κB/COX-2/CYP2E1 expressions.
Keywords: Sulforaphane; Losartan; Acrolein; Cardiomyopathy; Oxidative Stress; PPARγ; Nrf2